The adaptation of the beyond cold water bootcamp course for Inuvialuit communities in Northwest Territories, Canada. Issue 1 (1st January 2021) - Contini, Nia; Giles, Audrey R.; Giesbrecht, Gordon; Raddi, Tyrone
ABSTRACT: Boating-related fatalities in the Northwest Territories (NWT) are well above the national average. These fatalities are exacerbated by very cold water, and water and boating safety resources that lack relevance to residents of northern communities. We utilised an iterative, participatory approach to create a plain language, culturally and geographically adapted version of a cold water survival course, "Beyond Cold Water Bootcamp". The purpose of this research was to determine what adaptations are necessary to create appealing and pertinent boating safety interventions for Inuvialuit communities in the NWT and to demonstrate the value of generating such interventions. First, we conducted a focus group with boating safety experts to gain feedback on the first draft of the adapted course. We then subsequently completed a pilot of the course with community members in Tuktoyaktuk, NWT, and we obtained their feedback and suggestions. We then trained a local community member to deliver the course and conducted another focus group with residents. Using reflexive thematic analysis, our results demonstrated the value of culturally and geographically adapted boating safety interventions for Inuvialuit communities and the importance of relinquishing colonial power structures and enabling community members to independently adapt and disseminate knowledge.